Pengaruh Struktur Modal, Profitabilitas dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan - Putri, Adella; Syahzuni, Annis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of the exploration is to see whether or not the capital structure, profitability, and growth of the company have an influence on the value of the company in the transportation sector listed on the IDX in 2020 – 2022. The independent variables used in this exploration are Capital Structure (DER), Profitability (ROA), and Company Growth (Net Revenue Growth), while the dependent variable is Company Value (PBV). This exploration was conducted using a quantitative system using secondary data. The population data in this exploration uses 54 transportation subsector companies listed on the Indonesia Stock Exchange in 2020 – 2022. The exploration sample used intentional slice with destined criteria to gain 18 companies fiscal statement data. The data analysis system used is multiple direct retrogression analysis through the SPSS program. The independent variable used in this exploration only has a 9 impact on the value of the company. The results showed that profitability has a positive effect on the value of the company, while the capital structure and growth of the company don't affect its value. thus, it's recommended that farther exploration be carried out to consider other independent variables that affect the value of the company, similar as the size of the company, because the size of the company is a pivotal fiscal index for a company. Keywords: Capital Structure, Profitability, Company Growth, Company Value